EVALUASI KEANDALAN DESAIN FRESH AIR DAMPER 5J1S02 DAN 5J1S04 DI PABRIK SEMEN INDARUNG V - Santoro, Santoro; Amrina, Elita (Teknik Elektro Universitas Siliwangi, 2024)
One of the factory equipment that is very important in the cement production process is the suspension preheater used to heat cement raw materials before entering the rotary kiln for the combustion process or clinkerization process to produce clinker which in the next stage is ground into cement. In a suspension preheater kiln system, using a damper is vital because it regulates the flow of hot gas and material in the kiln and adjusts to the operating parameters of the equipment. Therefore, damper operation is reliable and meets safety regulations. One of the dampers used in the suspension preheater system at the Indarung V factory is a fresh air damper which functions to limit the temperature of the gas in the suspension preheater which will be pulled by the ID Fan so that overheating does not occur in the ID Fan impeller. In its operations, the fresh air damper at the Indarung V cement factory often experiences malfunctions caused by damage to the damper actuator due to exposure to heat from hot gases passed through the damper. This project aims to increase the reliability of the damper actuator and minimize maintenance costs, namely by modifying the mechanical power transmission design from the actuator to the damper shaft to reduce the impact of exposure to hot gases and modifying the actuator type from a modulating type to an open-close actuator type following operational needs and PUIL 2011, as well as to meet personnel safety needs. According to the results of commissioning tests and observations carried out from early August 2023 to November 2023, it was found that the test results and performance of the fresh air damper using the open-close actuator type damper functioned according to process requirements without experiencing damage to the actuator caused by exposure to heat in its operation.